Shelf slope convection: A note for antarctic regions - Piacsek, S.; Potts, M.; Castellana, L.; Purini, R. (Societa italiana di fisica, 2002)
Some basic processes associated with buoyancy-driven convection in the presence of coastal upwellingcurren ts were investigated in a 2.5D framework near the Adelie Coast of Antarctica. The surface buoyancy forcingw as derived from coolingand brine deposition due to ice formation, and was specified over a persistent off-shore polynya maintained by the off-shore katabatic winds. Rotational effects and the formation of a turbulent surface mixed layer were included in the model. The representation of topography was done via the VBM (virtual Boundary Method) that utilizes equivalent body forces in the momentum equation, thus enabling the use of very efficient Poisson solvers for the pressure, based on FFTs. The simulations were carried out near longitude 143E, between latitude 68S and 65S, over the nearshore shelf region. The hydrography was initialized with the 1/4 deg Levitus annual climatology. Two cases of idealized meteorological forcing were considered: constant winds blowingalong -shore and off-shore. The resultant motions in each case were characterized by interaction between the wind-driven upwellingmotions and the downward movingdense convection plumes, but with marked differences: a) the formation of a strongfron t under the open sea edge of the polynya only by off-shore winds; b) the periodic suppression of the surface off-shore currents and of the coastal upwelling only by the along-shore winds; c) the formation of deep upwelling currents along the slope between 400 and 200 meters only for along-shore winds, and d) the rapid filling of the surface layers (depths < 100m) with high salinities under the whole polynya by the off-shore forcing, vs. the delayed fillingof a narrow region near the downwellingplume with intermediate salinity values by the along-shore forcing.